Vertikale Desintegration des britischen Eisenbahnsektors. Erfolg oder Misserfolg? - Schnöbel, Christian R. (Deutscher Verkehrs-Verlag, 2005)
Die Bahnstrukturreform Großbritanniens bildet derzeit den Kristallisationspunkt der eisenbahnpolitischen Debatte um die Trennung von Netz und Transportbetrieb zu Gunsten eines funktionsfähigen intramodalen Wettbewerbs. Schließlich könnten die Bewertungen der britischen Bahnreform kaum unterschiedlicher ausfallen, sehen sich in ihrem Licht doch sowohl die Befürworter als auch die Gegner der vertikalen Desintegration in ihrer Haltung bestätigt. Der Beitrag ist ein Versuch der Klärung, ob die in Großbritannien durchgeführte Trennung von Netz und Transportbetrieb als Erfolg oder Misserfolg zu werten ist. difu

The structural reform of Britain's railway sector is the subject of controversy whenever policy matters are reviewed in connection with the separation of the rail track and operations sectors. It is worth noting that, since the adoption of restructuring measures for Britain's rail sector, the results have been notably better than those achieved by British Rail, while the modal split is viewed as exemplary in a Europe-wide context. Problems over proper coordination among the parties involved - especially with regard to the politics of investment - can be ascribed to a failure of government policies during the preparation, and realization, of reforms and cannot be accepted as a general argument against the separation of the rail track and operations sectors. Britain's rail reform has provided the evidence for the great potential of a 'road-rail system', which would be much enhanced by the opening up of rail transport markets to intra-modal competition by way of a vertical disintegration and the involvement of the private sector. difu
Keywords: Eisenbahn; Schienenverkehr; Personenverkehr; Güterverkehr; Verkehr; Verkehrsunternehmen; Staatsunternehmen; Privatisierung; Verkehrsinfrastruktur; Mangel; Bahnanlage; Bahnnetz; Bahnreform; Liberalisierung; Deregulierung; Verkehrsleistung; Modal-Split; Verkehrsmarkt